The Boundaries of Language: Dealing with Paralinguistic Features - Karpiński, Maciej (Lingua Posnaniensis, 2013)
The paralinguistic component of communication attracted a great deal of attention from contemporary linguists in the 1960s. The seminal works written then by Trager, Crystal and others had a powerful influence on the concept of paralanguage that lasted for many years. But, with the focus shifting towards the socio-psychological context of communication in the 1970s, the development of spoken corpora and databases and the significant progress in speech technology in the 1980s and 1990s, the need has arisen for a more comprehensive, coherent and formalised - but also flexible - approach to paralinguistic features. This study advances some preliminary proposals for a revised treatment of paralanguage that would meet some of these requirements and provide a conceptual basis for a new system of annotation for paralinguistic features. A range of views on paralinguistic features, which come mostly from the fields of speech prosody and gesture analysis, are briefly discussed. A number of assumptions and postulates are formulated to allow for a more consistent approach to paralinguistic features. The study suggests that there should be more reliance on continua than on binary categorisations of features, that multi-functionality and multimodality should be fully acknowledged and that clear distinctions should be made among the levels of description, and between the properties of speakers and the speech signal itself.